Perceptions, Expectations, Reality, and Public Confidence Regarding the Role of Pharmacists in Pharmacy Services in Bandung - Zazuli, Zulfan; Anjasmara, Aulia Putri; Amalia, Lia (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: The shifting from the old paradigm to the new paradigm with the philosophy of pharmaceutical care demands pharmacists to enhance the quality of pharmaceutical services. However, this role has not been optimally fulfilled, especially in the community setting.Objectives: This study aimed to identify the perceptions and expectations, the gap between expectations and reality, and public confidence as well as to analyze the relationship between sociodemographic factors and the perceptions, expectations, and public confidence in Bandung City regarding the role of pharmacists in pharmaceutical services.Methods: A cross-sectional study was conducted using a validated survey instrument with 440 respondents in Bandung, West Java, from March to April 2023. The survey data were analyzed descriptively and through inferential statistics.Results: The analysis showed that 58.41% of the community had a positive perception, 56.82% had high expectations, the average gap between expectations and reality was 14.04%, and more than 51.36% had a high level of public confidence in pharmacists. Sociodemographic factors influencing perceptions were age and the highest level of education (p = 0.005; p = 0.003), factors influencing public confidence were age, the highest level of education, residence address according to ID card (KTP), and occupation (p < 0.001; p = 0.034; p = 0.001; p = 0.001), and the factor influencing expectations was the residence address according to ID card (KTP) (p = 0.043). A correlation was found between the dimensions of perceptions, expectations, and public confidence.Conclusion: Most participants held a positive perception, had high expectations, and shown high confidence in the pharmacist's position, despite the existence of a disparity between expectations and the actual provision of pharmacy services. The elements of perception, expectations, and confidence are interrelated.